What a shame! - Abd Razak, Dzulkifli (2005)
THE Health Minister seemed irritated last week by tobacco companies negating the Government’s efforts to reduce the number of smokers. He may not have realised it it but this action by the tobacco companies is nothing new. According to a study published in the authoritative Tobacco Control Journal (December 2004), the socalled "negation" has been an ongoing strategy adopted by the industry since the 1970s. Perhaps the ministry has not taken this seriously or has been unaware of it and this has emboldened the industry to take part in the latest "sabotage".